2014
DOI: 10.3892/or.2014.3669
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein inhibits the invasion of gastric cancer cells by suppressing the activity of the p38 signaling pathway

Abstract: Baicalein, one of the major flavonoids in Scutellaria baicalensis, has been used in anti-inflammatory and anticancer therapies for a long time. However, the antimetastatic effects and related mechanism(s) in gastric cancer remain unclear. In the present study, we tested the hypothesis that administration of baicalein may inhibit the proliferation, motility and invasion of human gastric cancer cell lines by regulating the p38 signaling pathway. In the present study, we found that baicalein could inhibit migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 26 publications
0
29
1
Order By: Relevance
“…Signaling pathways are involved in its function of anti-CRC, including activation of the Nrf2 signaling pathway [27] and attenuation of the MAPKs and PI3K-Akt activation [28]. As for other common malignant tumors, several reports have revealed various kinds of signal paths mediated by baicalein [8,29,30]. In the most important part of our research, we examined the proliferation of HCT116 cell periods by CCK-8 assay and flow cytometry (FCM).…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways are involved in its function of anti-CRC, including activation of the Nrf2 signaling pathway [27] and attenuation of the MAPKs and PI3K-Akt activation [28]. As for other common malignant tumors, several reports have revealed various kinds of signal paths mediated by baicalein [8,29,30]. In the most important part of our research, we examined the proliferation of HCT116 cell periods by CCK-8 assay and flow cytometry (FCM).…”
Section: Discussionmentioning
confidence: 99%
“…This study provided the basic mechanism for baicalein’s inhibition of metastasis in gastric cancer cells by inactivation of the TGF-β/Smad4 pathway [43]. Similarly, another study revealed that baicalein inhibited the invasion of gastric cancer cells by inhibition of the p38 signaling pathway and subsequent MMP-2 and MMP-9 suppression [44]. Baicalein was reported to reverse hypoxia-induced 5-FU resistance in gastric cancer AGS cells.…”
Section: Baicalein and Gastric Cancermentioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK) signaling pathway is widely expressed in multicellular organisms, with critical roles in multiple biological processes, such as cell proliferation, migration, and invasion. The function of the three central kinases of the MAPK signaling pathway, ERK, JNK and p38 were all involved in the metastasis and invasion of gastric cancer [3639]. …”
Section: Discussionmentioning
confidence: 99%